2010
DOI: 10.1109/tbme.2010.2044176
|View full text |Cite
|
Sign up to set email alerts
|

Correntropy-Based Spectral Characterization of Respiratory Patterns in Patients With Chronic Heart Failure

Abstract: Abstract-A correntropy-based technique is proposed for the characterization and classification of respiratory flow signals in chronic heart failure (CHF) patients with periodic or nonperiodic breathing (PB or nPB, respectively) and healthy subjects. The correntropy is a recently introduced, generalized correlation measure whose properties lend themselves to the definition of a correntropybased spectral density (CSD). Using this technique, both respiratory and modulation frequencies can be reliably detected at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
1
25
0
4
Order By: Relevance
“…In our recent studies [20] and [21], the ratio between the powers in the modulation and respiratory frequency bands R provided an accuracy of 88.9% when classifying PB versus nPB. In this study, we have observed that the ratio R extracted from the original signal and the one extracted from its surrogate data present significant differences in nPB patients, but not in PB patients, thus reflecting a higher degree of nonlinearity in nPB patterns.…”
Section: Discussionmentioning
confidence: 87%
“…In our recent studies [20] and [21], the ratio between the powers in the modulation and respiratory frequency bands R provided an accuracy of 88.9% when classifying PB versus nPB. In this study, we have observed that the ratio R extracted from the original signal and the one extracted from its surrogate data present significant differences in nPB patients, but not in PB patients, thus reflecting a higher degree of nonlinearity in nPB patterns.…”
Section: Discussionmentioning
confidence: 87%
“…Also, the multivariate logistic regression model developed using features extracted from CSD-based analysis provided better classification results, in terms of accuracy, sensitivity, specificity and AUC, than the model created with PSD-based features. The reason for this improvement could be the capability of the correntropy, and subsequently CSD, to preserve nonlinear characteristics and high-order moments of the data [16,28,29], in this case PPIs, which have been previously documented as chaotic or nonlinear [11,12]. In addition, we justified the use of CSD by demonstrating that the majority of the patients showed evidence of nonlinear PPIs behaviour.…”
Section: Discussionmentioning
confidence: 78%
“…Decreases in entropy of cardiac interbeat intervals have also been observed in conditions of cardiovascular stress associated with heart failure [16,30] at rest, and even in heart failure patients performing their usual daytime activities [6].…”
Section: Discussionmentioning
confidence: 94%
“…These results improved by applying a nonlinear spectral characterization to the respiratory flow signal through the innovative correntropy function [16]. In that database, the respiratory flow signal of heart failure patients at rest was acquired using a pneumotachograph.…”
Section: Discussionmentioning
confidence: 99%